2009
DOI: 10.1021/ja903511s
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of an Intramolecular Frustrated Lewis Pair with Unsaturated Substrates: Evidence for a Concerted Olefin Addition Reaction

Abstract: The intramolecular frustrated Lewis pair (mesityl)(2)P-CH(2)-CH(2)-B(C(6)F(5))(2) was generated in situ by HB(C(6)F(5))(2) hydroboration of dimesitylvinylphosphine. The compound reacts with 1-pentyne by C-H bond cleavage. It undergoes a 1,2-addition to the carbonyl group of trans-cinnamic aldehyde to yield a zwitterionic six-membered heterocycle by B-O and P-C bond formation. The Lewis pair regioselectively adds to the electron-rich C=C double bond of ethyl vinyl ether, and it selectively undergoes an exo-cis-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
1
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(91 citation statements)
references
References 148 publications
3
82
1
5
Order By: Relevance
“…[109] Similarly, the species t Bu 3 P(N 2 O)B(C 6 H 4 F) 3 (136) was prepared and used in Lewis acid exchange reactions to give a variety of analogues including the exchange of the weak Lewis acid for other more electrophilic boranes. [109] For example, treatment with a variety of boranes gave (140).…”
Section: Hidden Flpsmentioning
confidence: 99%
See 1 more Smart Citation
“…[109] Similarly, the species t Bu 3 P(N 2 O)B(C 6 H 4 F) 3 (136) was prepared and used in Lewis acid exchange reactions to give a variety of analogues including the exchange of the weak Lewis acid for other more electrophilic boranes. [109] For example, treatment with a variety of boranes gave (140).…”
Section: Hidden Flpsmentioning
confidence: 99%
“…[11,136] An intramolecular version of this reaction was probed by bridged vinylphosphine/borane systems generated in situ by HB(C 6 F 5 ) 2 hydroboration of the aryldivinylphosphine bearing the bulky 2,4,6-tri-tert-butylphenyl ("supermesityl") substituent. Interestingly, the simple hydroboration product was not observed, rather the heterocyclic, intramolecular zwitterionic methylenephosphonium derivative 198 is obtained (Scheme 69).…”
Section: Flp Routes To Borata Alkenesmentioning
confidence: 99%
“…A number of experiments have demonstrated that the special nature exactly results in the activation of H 2 [3,4,[8][9][10][11][12] and other small molecules, such as THF [13,14], N 2 O [15], olefins [16,17], terminal alkynes [18,19], catechol boranes [20], dienes [21], amine [22,23], and so on [5,24,25], as well as applications in catalysis simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, another analogous sterically hindered N-heterocyclic carbene borane [9,27] has been synthesized and the literature reported that one FLP compound containing N-heterocyclic carbene was also capable of reacting with CO 2 , CO, olefin, phenylacetylene, etc. Although several papers have been published in order to consider the mechanisms of the reactions between phosphane and borane compounds and H 2 , or the other small molecules [17,24] by the method of quantum computation [23], nevertheless, little work has been carried out for the mechanisms of the analogous N-heterocyclic carbene borane towards them, especially the small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Within the expanse of such compounds, phosphinoboranes are unique because they contain tethered nucleophilic phosphorus and electrophilic boron centers, typically in close proximity [4,5,6,7,8,9,10,11]. The ambiphilic ligand properties of phosphinoboranes have been exploited in CO reduction and the modeling of alkyl-abstraction schemes related to ZieglereNatta catalysis [12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%